The Urgency of Child Grooming Regulation in the Legal System in Indonesia - Kinanti Alysha Putri Haryanto,; Beniharmoni Harefa, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
Child grooming is a legal issue that has negative consequences for children, especially which in a victimized position. However, there are no regulations in Indonesia that specifically regulate these legal issues. Even while there are positive laws that can be used as a basis for criminalizing groomers, it turns out that law enforcement still faces a number of obstacles. In this case, a normative juridical methodology based on a statute approach, a case approach, a literature approach, a conceptual approach, and a comparison approach was used to conduct the research. Based on research studies, data collection is carried out. This research demonstrates that there are still obstacles to Indonesian child grooming legislation enforcement, which are quite often related to the evidence process. Alternative regulations against child grooming as stated regarding the positive laws above, such as ITE Law, Child Protection Law, and Pornography Law have gaps that have been found to lead to other issues, such as disparities in punishment. The TPKS Law and the Indonesian Criminal Code Bill could be other options that may one day be considered in cases involving child grooming. It ought to be striving for special regulations against child grooming. In such cases, it would appear that it would be preferable if they were made into technical regulations in the form of government regulations with proof and criminal sanctions that were more maximized. Keywords: Child Grooming; Regulations; Law Enforcement